AN ANALYSIS OF STUDENTSâ DIFFICULTIES IN TRANSLATING DESCRIPTIVE TEXT (A CASE STUDY AT FIRST SEMESTER OF CATHOLIC UNIVERSITY OF SAINT THOMAS MEDAN) - Tarigan, Karisma Erikson (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
The Objective of this study entitled âAn Analysis of Studentsâ Difficulties in Translating Descriptive Text (A Case Study at First Semester of Catholic University of Saint Thomas Medan)â was to identify, classify and describe the studentâs difficulties in translating descriptive text. The subject of this study was twenty two students at the first semester of Catholic University of Saint Thomas Medan. The writer used the test as an instrument. In collecting the data the students translated the descriptive text. The result of this study showed that the students found the difficulties in syntactic ambiguity in sentence and sequence of word meaning 51% in the form of adjective (95%), Noun Phrase (86%).Keywords: Difficulties, Syntactic Ambiguity, Translation.